THE LESSON FROM DEMAND RESPONSE IN JAPAN - Lee, Hyunyoung (PEOPLE: International Journal of Social Sciences, 2017)
This study aims to contribute to Japanese policy recommendations with using the concept of ‘Nudge’ aimed at encouraging DR adoption that is scheduled for the wholesale electricity market starting in April 2017. Because consumers have bounded rationality, if the concept of Nudge is added to DR, there is a possibility of expanding the participation in DR more widely. In this paper, we reviewed Japanese electricity demand reduction efforts (the voluntary program) and demonstrated projects with using the nudge concept. The study found that the concept of nudge was useful in both DR trials. However, there was also the problems in these projects. The problem with the voluntary program was that when the consumer believed there was sufficient electricity, they were less willing to cooperate. The problem with the demonstration projects was the relatively low participation rate. Therefore, what the government needs to do is to assist consumers in understanding the importance and the necessity of DR, and in this education process, the Japanese government could use the nudge concept by reflecting on lessons from experiences in Japan and abroad.